A Comparison of Pan & Kosicki's Framing Syntactic Structures in Reporting on the Fake Joko Widodo 2025 Diploma Case in Electronic Media - Siti Nurhalisa Pobela; Sitti Rachmie Masie; Herman Didipu (Raja Zulkarnain Education Foundation, 2026)
This study aims to compare the syntactic structures of Pan & Kosicki's framing in reporting on the fake Joko Widodo 2025 diploma issue on Kompas.com and Tribunnews.com. The research was conducted online from April to May 2025 through access to both media sites. The study population was all news articles related to the fake Joko Widodo 2025 diploma issue, with a sample of eight articles (four articles per media) purposively selected based on the following criteria: thematic relevance, balance in quantity, and publication timeframe. The research instrument was a framing analysis sheet based on the Pan & Kosicki model, which focuses on five elements of syntactic structure: headline, lead, background information, source quotations, and conclusion. The data analysis technique was carried out by adapting the Pan & Kosicki framing model with the following steps: reading techniques, note-taking techniques, identification of syntactic elements, categorization and interpretation, and comparative analysis between Kompas.com and Tribunnews.com. The results of the study show that Kompas.com tends to build legal-formal and pro-legitimacy framing with the following characteristics: informative-procedural titles (the word